Breaking the news : what's real, what's not, and why the difference matters - Brown, Robin Terry (National Geographic, 2020)
Traces the history of gathering and disseminating news, from spoken and written accounts, to mass distribution through the printing press, radio, television, and internet. Discusses propaganda, freedom of speech, notable journalists, political images, conspiracy theories, ethics, and how to distinguish fake websites, phony photos, biases, and fabricated sources. Includes a quiz, interactive prompts and tips, color photographs, fact boxes, biographical sketches, a timeline of major events in news history, and other infographics.